2003
DOI: 10.1016/s0920-5632(03)80370-5
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic ray astrophysics and hadronic interactions

Abstract: Research in cosmic rays is now nearly a century old, but most of the fundamental questions in this field remain unanswered, on the other hand the perspectives of future studies in the next decade are very bright. New detectors will provide higher quality data in the entire energy range from 10 8 to 10 20 eV (or more if particles of higher energy have non negligible fluxes), moreover cosmic ray astrophysics must now be considered, together with gamma, neutrino and gravitational wave astronomy, as one of the sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…are independent of √ s (Lipari 2003). The ISR data are, in fact, well described by such scaling: the cross-section for leading neutron production was found to fall off exponentially in p ⊥ for fixed Feynman x F and could be parameterized by equation ( 48) with b parameter of (4.8 ± 0.3) (GeV/c) −1 , independent of s and x F in the range 0.2 ≥ x F ≥ 0.7 (Engler et al 1975).…”
Section: Theory At Low Energies and The Interpretation Of The Isr Datamentioning
confidence: 98%
See 3 more Smart Citations
“…are independent of √ s (Lipari 2003). The ISR data are, in fact, well described by such scaling: the cross-section for leading neutron production was found to fall off exponentially in p ⊥ for fixed Feynman x F and could be parameterized by equation ( 48) with b parameter of (4.8 ± 0.3) (GeV/c) −1 , independent of s and x F in the range 0.2 ≥ x F ≥ 0.7 (Engler et al 1975).…”
Section: Theory At Low Energies and The Interpretation Of The Isr Datamentioning
confidence: 98%
“…Clearly if Feynman scaling always held exactly one could easily extrapolate low energy results to predict the properties of hadronic interactions at an arbitrarily high energy. Data obtained on pp interactions in general (conducted since the ISR experiments) at SppS, Tevatron and RHIC, however, have shown that Feynman scaling is violated with, in particular, both the afore-mentioned, slow cross-section growth and some evolution of secondary, charged particle multiplicity evident in the data (Lipari 2003). This can be naturally interpretted as symptomatic of the fact that at increasingly high 'probe' momenta, the detailed QCD structure of the hadron is progressively revealed (i.e., the description of the proton as a bag of three valence quarks breaks down).…”
Section: Extrapolating Multiplicity and Elasticity To High Energies: ...mentioning
confidence: 98%
See 2 more Smart Citations
“…where L is the integrated luminosity. Now, following [124,125], we can obtain the total cross section independently from L, by using σ tot = (σ el + σ inel ) = (N el + N inel )/L,…”
Section: B Hadronic Interactions In the Earth's Atmospherementioning
confidence: 99%